FORMATION OF CONSUMER PROPERTIES OF ELASTIC LEATHER MATERIALS - DANYLKOVYCH, ANATOLII; LISHCHUK, VICTOR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
For the effective use of leather material by the consumer, not only the physical and mechanical properties stipulated by the standard are taken into account, but also the hygienic and aesthetic ones, the role of which is determined by the technological features of manufacturing and operating conditions of the corresponding products. In this regard, there is a need for a comprehensive study of the consumer properties of leather materials, which determine their product quality and value for the consumer. The purpose of the study is to determine the technological features of the formation of consumer properties of elastic leather materials. At the same time, the following tasks were implemented: the filling and finish tanning of the leather semi-finished product of chrome tanning for the elastic material of the model and special purpose shoe upper; a coating is formed on the material for model shoes; consumer properties of leather material for model and special-purpose shoes are established. Research methods: consumer properties of leather materials were determined by a complex of physical-chemical, photographic and organoleptic methods. Research results. The influence of coating compositions based on polyurethane, polyacrylurethane and modified polyacrylate on the complex of physical-chemical and hygienic properties of leather material was investigated. It has been established that leathers with polyacrylic urethane finishing are characterized by high values of physical and mechanical and especially hygienic properties. Finishing of the frontside surface of the semi-finished product with the use of a polyacrylic urethane composition makes it possible to form a leather material of a wide range of colors with consumer properties that determine its intended use.